Ethical security studies a new research agenda - Nyman, Jonna; Burke, Anthony (Routledge critical security studies series, 2016)
The ethics of security represent one of the crucial issues of our time. This sophisticated, challenging and wide-ranging collection demonstrates the theoretical challenges and practical value of placing ethical questions at the center of security, as well as the pressing need to do so. The contributions challenge us to take seriously a range of perspectives, from anti-security and posthuman security to emancipatory security or security cosmopolitanism. The book will reinvigorate debates about the analytical and political concepts deployed in critical security studies.